Tropical pyomyositis of the flexor digitorum superficialis with “pointing finger” sign in a child - Liew, Siew Khei; Saaid, Firdati Mohamed; Looi, Collin Seng Kim; Arumugam, Manohar (World Scientific Publishing Co. Pte. Ltd., 2022)
Tropical pyomyositis (TP) of the upper limb is uncommon, especially in forearm and hand. The incidence was around 2.2% of paediatric TP. Cases reported in the literature were from pre-school and school age children. We describe a case of an 11-month-old girl with concurrent dengue fever and Staphylococcus aureus bacteraemia who presented with TP of flexor digitorum superficialis showing “pointing finger” sign of the hand. She was treated with surgical drainage and antibiotics and recovered well. This case describes a new clinical sign for tropical pyomyositis of the flexor muscles in the forearm in a young child and the challenges in making the clinical diagnosis.